Tax Avoidance and Firm Value of Selected Firms in Nigeria - Malobi Gladys Okolie; Moses Onyeka Chukuwendu (CV. Proaksara Global Transeduka, 2025)
This research investigates the relationship between tax avoidance strategies and company value among publicly traded non-financial corporations in Nigeria. The researchers developed two hypotheses to guide their investigation and utilized an ex-post facto research approach. They measured firm value using Tobin's Q as the outcome variable, while examining book-tax differences and cash effective tax rates as the key explanatory factors. The analysis focused on 76 publicly listed non-financial companies from the Nigerian Exchange Group, covering a ten-year period from 2014 to 2023. The researchers applied feasible generalized least squares regression analysis using STATA 14.2 software to process the data. The results revealed that book-tax differences significantly influence Tobin's Q among the studied Nigerian non-financial firms (with statistical significance at p < 0.05). However, cash effective tax rates showed no meaningful impact on firm value (p > 0.05). Based on these findings, the researchers suggest that companies should prioritize strategic tax planning to better manage disparities between book and tax reporting, which could improve their perceived financial performance and boost investor confidence.